RATIO DECIDENDI PUTUSAN NOMOR 99/PID.SUS/2022/PN.PNG TERHADAP PERKARA TINDAK PIDANA NARKOTIKA GOLONGAN I BAGI DIRI SENDIRI - Khusnul Khofifah; Yusron Marzuki (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The imposition of narcotics crimes still reaps controversy in law enforcement due to the legal certainty of regulations regarding narcotics abuse regulated in Law Number 35 of 2009 concerning Narcotics by classifying the perpetrators, actions, and suitability of the sentences imposed. However, since the existence of the Supreme Court Circular Number 4 of 2010 concerning the Placement of Narcotics Addict Victims of Abuse in Institutions for Medical Rehabilitation and Social Rehabilitation. It has the possibility for narcotics addicts themselves to obtain medical rehabilitation by a judge's Considerations on decision. This will be examined in the research object of Decision Number 99/Pid.Sus/2022/PN.PNG as the judge sentenced him to imprisonment instead of rehabilitation, therefore this study uses a normative method, which is descriptive-analytic in nature, namely research that is discussed and analyzed from general matters to conclusions. The sources of legal materials used in the research contain primary and secondary data, then an approach is made using a statutory approach (statue approach), conceptual approach (conceptual approach), and case approach (case approach).